Intention to adherence to social distancing for prevention of Covid-19 in the urban areas of southern Iran: a structural equation modeling (SEM) analysis of theory of planned behavior - Tayebeh Rakhshani; Victoria Momenabadi; Abdolrahim Asadollahi; Ali Khani Jeihooni (BMC, 2024)
Abstract Background Social distancing is a key behavior to minimize and controlling COVID-19 infections. The current study applied an integrated Theory of Planned Behavior to identify the determinants of social distancing behavior, and the processes involved, in the context of the COVID-19 pandemic. Methods a cross-sectional study was conducted in Southern Iran among 1000 people from Shiraz by employing a convenience sampling technique. Data were collected using a pre-tested and structured questionnaire based on the main constructs of the Theory of Planned Behavior. Statistical analysis was done using IBM SPSS software version 22 and Amos version 24. Level of statistical significance was declared at a P-value of less than 0.05. Results according to the results, the subjective norms (F = 2.696, effect size = 0.139) and attitude (F = 3.582, effect size = 0.155) play an important role in the samples' PBC (P ≤ 0.05). Final adjusted structural equation model of the effects of independent variables (Gender, subjective norms, attitude) on samples' intention to adherence social distancing for prevention of Covid-19 with the mediating role of one main variable of PBC. The PBC alone can be an important factor in creating intensive behavior in the samples (F = 3.560, effect size = 0.18). Conclusion current findings highlight the importance of "attitude, subjective norms and PBC" as determinants of social distancing intention. Future research on long-range predictors of social distancing behavior and reciprocal effects in the integrated model is warranted. This evidence is relevant to public and private organizations in the process of developing strategies to promote and engage the population in adopting the behavior of "Adherence to Social Distancing" in Iran.